Geochronology and Geochemistry of Late Paleozoic Volcanic Rocks and Their Relationship With Iron and Molybdenum Deposits in Xilekuduk Area, Northern Margin of Junggar - Wei, Xiaofeng; Wei, Hao; Liao, Zhen; Wang, Zhiwei; Li, Dong; Mao, Qigui; Li, Xiao (Frontiers in Earth Science, 2021)
A large number of intermediate basic volcanic rocks and porphyry Cu-Mo deposits as well as volcanic hosted mgagnetite deposit have been recently discovered in the Xilekuduk area. However, no reports concerning petrogenesisdiagenetic characteristics and age, or their relationship with mineralization have been published to date. The purpose of this study is to make up for the absence of previous studies on Devonian volcanic activities in the area and to confirm the relationship between two stages of volcanic activities and mineralization so as to provide important theoretical basis for mineral exploration. Based on research results of zircon U-Pb geochronology and element geochemistry of volcanic rocks in the area, the ages of dacite, andesite and stomatal andesite are considered as 375.2±2.9Ma, 386.5±3.0Ma, and 317.9±2.9Ma respectively, corresponding to the Middle Devonian and Late Carboniferous. The Devonian volcanic rocks belong to the high-Kk calc alkaline series and island arc volcanic rocks, which are enriched in LREE, strongly enriched in large ion lithophile elements Th, Rb, Ba and K, and relatively depleted in high field strength elements (HFSEs)high field elements Na, TaNb, Ta and Ti. The Carboniferous volcanic rocks are enriched in LREE, as well asbelong to the LREE enrichment type, and the large ion lithophile elements Th, Rb, Ba and K are strongly enriched, while depleted in the HFSEshigh field elements Na, TaNb, Ta and Ti, are relatively depleted; moreover, the contents of TiO2 and V are 0.94-0.97% and 178-183×10-6, which are higher than those of island arc basalts. According to mineralogical typomorphic characteristics and geochemical analysis, magnetite mineralization is divided into two phases. The early stratiform magnetite ore MT1 has magmatic characteristics, forming a volcanic rock type magnetite deposit related to Devonian Volcanic eruption and sedimentation (375-386Ma). The magnetite MT2 in the magnetite-quartz vein is considered as hydrothermal genesis, which is a metal mineral in the early metallogenic stagestage of of Carboniferous (317.1±2.9Ma) volcanic eruption and subvolcanism, and may be related to porphyry molybdenum mineralization. Therefore, the volcanism and Fe-Cu-Mo mineralization in this area is characterized by multi-stage superimposed mineralization.